The Microeconomic foundations of macroeconomics : proceedings of a conference held by the International Economic Association, at S'Agaro, Spain - Harcourt, G. C.; International Economic Association (LON The Macmillan Press Limited, 1977)
Includes bibliographical references and index.
Conference held Apr. 1975. and has footnotes
mf 25/01/2019
This book touches the use of Keynesian analysis in economic issue and aggregated the problems of macroeconomics.
Keywords: Economics; Microeconomics; Macroeconomics; S'Agaro, Spain